Analysis of Queue Decomposition Time Due to Railway Crossing Gate Closure to Avoid Dissaster - Waluyo, Waluyo; Bihtiari, Adib Mufti; Sukatiman, Sukatiman (ASTONJADRO, 2026)
This research was conducted on a segment of railway at HOS Cokroaminoto Road which aims to analyze: (1) Traffic volume; (2) Delay and queue occurred due to the at-grade railway crossings; (3) Level of service; (4) Queue decomposition time due to railway crossing gate closure. The population of this research are the traffic data at an at-grade crossing in Surakarta City and the sample of this research are at-grade crossing traffic data on HOS Cokroaminoto Road segment, in Surakarta. The sampling technique used is purposive sampling technique. The data in this research is analyzed by applying inferential analysis. The research results are as follows: (1) The average traffic volume is 577,538 PCU/hour from north to south direction and 222,025 PCU/hour from the opposite direction. (2) The average delay occurred is 219,058 seconds on the north to south direction and 227,025 seconds on the opposite direction. The average of the queue length occurring is 95,25 meters on the north to south direction and 97,048 meters on the opposite direction. (3) The level of service based on the daily traffic volume is on A level on both directions, while based on the traffic volume during the at-grade railway crossing closure is on F level. (4) The average of queue decomposition time due to the at-grade railway crossing closure is 91,0833 seconds from north to south direction and 98,325 seconds from the opposite direction.